(3QSGFd GHf GdbGVi GdaGVds - (3CHh Ydj YHO GdQMje Hf Ydj Hf GdSYjO GddNei GdHjSGfi , GdeYQha HGdbGVi GdaGVds; (3GdbGVj GdaGVd , eMjj GdOjf CHh Ydj,J (B596 (3g` s
(3ChdgG (B:s
(3cJGH Edi Gdedc GdCaVd QMeg Gddg(B: (3COGe Gdg OhdI ehdGfG hTjO CQcGfgG hCYR SdWGfgG hYeQ HGdSYGOI ChWGfgG dYd GdeSGaI CbQH hGdhbJ jWjH hGdKdL jQJaY hGdWQjb jSdc GdEQLGa jfbWY , GdVYa GdPi Ydjg jba s
(3BNQgG (B:s
(3cJGH Edi Gdedc GdCaVd QMeg Gddg(B: (3COGe Gdg OhdI ehdGfG hTjO CQcGfgG hCYR SdWGfgG hYeQ HGdSYGOI ChWGfgG dYd GdeSGaI CbQH hGdhbJ jWjH hGdKdL jQJaY hGdWQjb jSdc GdEQLGa jfbWY , GdVYa GdPi Ydjg jba s
(3cJGH Edi Gdedc GdCaVd QMeg Gddg(B: (3COGe Gdg OhdI ehdGfG hTjO CQcGfgG hCYR SdWGfgG hYeQ HGdSYGOI ChWGfgGs
(3dYd GdeSGaI CbQH hGdhbJ jWjH hGdKdL jQJaY hGdWQjb jSdc GdEQLGa jfbWY GdVYa GdPi Ydjg jbas
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B346 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B209s
Keywords: (3GdCOHs